Preparation and evaluation of amphiphilic macromolecules-based conjugates and micelles for anticancer drug delivery - Del Rosario, Leilani Singson (ProQuest LLC, 2009)
Micelles assembled from amphiphilic macromolecules (AM) or drug-conjugated AMs were evaluated as anticancer drug carriers in terms of drug content, sustained/controlled drug release and cytotoxicity of encapsulated/bound drug. Physical drug encapsulation was compared with chemical drug conjugation. The AM micelles were compared with known polymeric delivery systems, Pluronic P85 and Cremophor EL. Generally, AM micelles encapsulated drugs as efficiently (or better) than the established polymeric carriers. Encapsulated hydrophobic drugs in AM micelles showed non-aggregation of drug and sustained drug release after lyophilization and resolubilization in aqueous solutions; indicating good solution and storage stability of drug-loaded AM micelles. Compared to the polymeric controls, the AM micelles showed faster resolubilization times and better pH/temperature micellar stability. Cellular entry of AM micelles in human umbilical vein endothelial cells was observed to be endocytotic, observed from the colocalization of fluorescein-labeled AMs and fluorescent dye-stained endosomes or lysosomes that were detected by confocal scanning microscopy. Doxorubicin (DOX) was conjugated to AMs via acidic pH-sensitive hydrazone linkers and the DOX-AM micelles had ~ 30 nm sizes. DOX-AMs showed higher drug release at lysosomal pH 5.0 as compared to physiological pH 7.4. Cell proliferation assays of DOX-AM micelles showed better cytotoxicity compared to DOX-loaded AM micelles and free DOX against human hepatocellular carcinoma cells. As another example of drug conjugation, camptothecin (CPT) was conjugated to AMs via glycine linkers. CPT-AM micelles showed CPT lactone stabilization, higher CPT solubilization, and increased stability against human serum albumin (HSA) on CPT release in vitro. However, cell proliferation assays on the CPT-AM micelles showed comparable cytotoxicity to CPT-loaded AM micelles against human colorectal carcinoma cells. The placement of CPT conjugation was evaluated by CPT conjugation via mucic acid and functionalized alkyl chains. Carbodiimides were used to conjugate CPT to AM mucic acid, whereas click chemistry conjugated alkyne-terminated CPT to azideterminated AM chains. Higher CPT conjugation was achieved via the functionalized chain ends (i.e. click chemistry) compared to the mucic acid (carbodiimide coupling). However, lesser HSA impact on CPT in vitro release was observed in CPT attached to the mucic acid. Overall, the AM-based micelles showed good characteristics as anticancer drug carriers.